Comprehensive Analysis and Expression Profiling of PIN, AUX/LAX, and ABCB Auxin Transporter Gene Families in Solanum tuberosum under Phytohormone Stimuli and Abiotic Stresses - Chenghui Yang; Dongdong Wang; Chao Zhang; Minghui Ye; Nana Kong; Haoli Ma; Qin Chen (Biology, 2021)
Auxin is the only plant hormone that exhibits transport polarity mediated by three families: auxin resistant (AUX) 1/like AUX1 (LAX) influx carriers, pin-formed (PIN) efflux carriers, and ATP-binding cassette B (ABCB) influx/efflux carriers. Extensive studies about the biological functions of auxin transporter genes have been reported in model plants. Information regarding these genes in potato remains scarce. Here, we conducted a comprehensive analysis of auxin transporter gene families in potato to examine genomic distributions, phylogeny, co-expression analysis, gene structure and subcellular localization, and expression profiling using bioinformatics tools and qRT-PCR analysis. From these analyses, 5 StLAXs, 10 StPINs, and 22 StABCBs were identified in the potato genome and distributed in 10 of 18 gene modules correlating to the development of various tissues. Transient expression experiments indicated that three representative auxin transporters showed plasma membrane localizations. The responsiveness to auxin and auxin transport inhibitors implied their possible roles in mediating intercellular auxin homoeostasis and redistribution. The differential expression under abscisic acid and abiotic stresses indicated their specific adaptive mechanisms regulating tolerance to environmental stimuli. A large number of auxin-responsive and stress-related cis-elements within their promoters could account for their responsiveness to diverse stresses. Our study aimed to understand the biological significance of potato auxin transporters in hormone signaling and tolerance to environmental stresses.